DEVELOPMENT OF STS MARKERS FOR WAXY GENE ALLELIC VARIATION IDENTIFICATION IN FOXTAIL MILLET - X. P. Jia; P. H. Dong; F. Y. Yu; J. Z. Quan; H. Bai; Z. P. Dong (Journal of Animal and Plant Sciences, 2015)
Waxy gene controls synthesis of amylose, having important application value in crop eating quality improvement. The waxy gene of foxtail millet has been cloned and sequenced. All the waxy and low-amylose types arose by the insertions of transposable elements into the waxy gene. Based on the sequence variation information caused by transposon insertions, 6 pairs of STS primers were designed to detect 10 allelic variation types of the waxy gene in eleven foxtail millet strains. The results showed that waxy allelic variation types of nine strains could be determined, they were “Xinji” sticky millet (IV/IV), Green sticky millet (IVa/ IVa), “Shanxi” sticky millet (VII/Wild), “Anyanghong” sticky millet (IV/IV), Jite5 (IV/III), Jigu30 (IV/V), Yellow sticky millet (IVa/ IVa), “Linxian” black sticky millet (IV/ VII), “Xincai” sticky millet (VII/ Wild). Two modern varieties Jigu19 and “Early white waxy” detected three allelic variation types (IVa, III, V), the real reason need be further investigated. No X, VI, VIII variation types were detected in the eleven foxtail millet strains. The developed STS markers were powerful in detecting which of the 10 waxy allelic variation types existed in any foxtail millet strain though iodine blue staining amylose determination technology needed when distinguish homozygous variation types from heterozygotes of variation type and wild type because of dominant markers.
Keywords: Foxtail millet; Eating quality; Waxy gene; Allelic variation; STS marker